The critique of pure reason - Kant, Immanuel (Kant, Immanuel, 1998)
"The most accurate and informative English translation of Kant's most important philosophical work in both the 1781 and 1787 editions; faithful rendering of Kant's terminology, syntax, and sentence structure; a simple and direct style suitable for readers at all levels; distinct versions of all those portions of the work substantially revised by Kant for the 1787 edition; all Kant's handwritten emendations and marginal notes from his own personal copy reproduced for the first time in any edition, German or English; a large-scale introduction providing a summary of the structure and arguments of the Critique as well as the most informative account available in English of its long and complex genesis; and an extensive editorial apparatus including informative annotation and glossaries."--BOOK JACKET.